PENGEMBANGAN MEDIA PEMBELAJARAN POP-UP BOOK BERBASIS KEARIFAN LOKAL PADA PEMBELAJARAN IPAS DI KELAS V SDN 107405 SEI ROTAN T.A 2024/2025 - Nurasnaini; Nurmayani (STKIP Subang, 2025)
This study aims to determine the feasibility, practicality, and effectiveness of a pop-up book learning media based on local wisdom for IPAS (Science and Social Studies Integration) learning in Grade V at SDN 107405 Sei Rotan. This research is a research and development (R&D) study using the ADDIE model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The feasibility of the product was determined through expert validation, with material expert validation scoring 85.8%, categorized as